Isolator-based point-of-care manufacturing: a practical solution for GMP-compliant cell and extracellular vesicles therapy production - Chiu, Yu-Sung; Wang, Kun-Liang; Wu, Kun-Lieh (Frontiers in Bioengineering and Biotechnology, 2025)
Cell and extracellular vesicle (EV)-based therapies represent a promising frontier in regenerative medicine and immunotherapy. However, their clinical translation is often constrained by the complexities of Good Manufacturing Practice (GMP)-compliant production, particularly under centralized manufacturing models. This Perspective discusses the emerging role of decentralized, point-of-care (POC) manufacturing in enabling timely, scalable, and patient-specific delivery of cell and EV therapeutics, with a focus on isolator-based systems as core manufacturing infrastructure. We discuss current advances in closed-system technologies, regulatory frameworks, and quality control (QC) strategies supporting GMP compliance in decentralized environments. Real-world applications and case studies illustrate feasibility and translational impact. Isolator-based platforms offer modular, sterile, automation-compatible environments that support both autologous and selected allogeneic product manufacturing at clinical sites. These systems reduce contamination risks, lower facility requirements, and enable integration with real-time QC testing. Despite these advantages, challenges remain, including regulatory ambiguity, workforce training limitations, and quality assurance gaps in decentralized settings. Emerging solutions include automated closed-system bioreactors, digitalized QC workflows, and harmonized operational standards to ensure product safety and consistency. Strategic coordination among regulators, hospitals, and developers will be essential to overcome operational and compliance hurdles. With appropriate infrastructure, skilled personnel, and standardized processes in place, isolator-based POC manufacturing holds the potential to transform how advanced therapies are produced and delivered—ultimately enhancing patient access to safe, effective, and personalized cell and EV-based treatments.